Family farming systems: An index-based approach to the drivers of agroecological principles in the southern Andes - Cortes, Josefina; Vieli, Lorena; Ibarra, Jose Tomas (My University, 2023)
Global social-ecological crises call for the identification and promotion of resilient agrifood systems. Agroecology can help addressing these challenges by fostering high levels of diversity and climate resilience. The application of agroecological principles (i.e. social-ecological processes translated into practices with positive effects on the conservation, stability and resilience of agriculture), increases systems' response capacity and ability to adapt to crises. Agroecology has its roots in indigenous agriculture but social-ecological filters (i.e. human-nature factors that remove or reinforce agroecological practices) may be, at times, shifting away these systems from agro-ecological principles. The dynamism of territories has prompted the arrival of new actors to rural areas such as lifestyle migrants. In this study, we assess the extent to which agroecological principles are present in family farming in the southern Andes and identify factors that can act as "social-ecological filters" of management practices, affecting the level of agroecology in these systems. We applied questionnaires to 80 gardeners (40 campesinos and 40 migrants), asking about 35 management practices and their socio-demographic profiles. We developed an Index of Agroecological Principles (IAP) to estimate the presence/absence of management practices that contribute to seven agroecological principles (four biological and three sociocultural). Most principles showed a presence over 0.5 (50%). We found a positive relationship between biological and cultural principles (r = 0.56; p < 0.01). Biodiversity was the principle with the highest presence (0.72&PLUSMN; 0.01). The value of the IAP was higher for indigenous and non-indigenous campesinos (4.5&PLUSMN; 0.1; ss = 4.27) than for migrants (3.9&PLUSMN; 0.12; ss =-0.4). The origin of the gardener, the age of the homegarden and the size of the farm, were the most influential social-ecological filters that selectively remove or reinforce agroecological practices in homegardens. We discuss the potential of an Index of Agroecological Principles in homegarden management for strengthening agroecology and resilience to social-ecological changes in a Global Biodiversity Hotspot and beyond.
Keywords: homegardens; index of agroecological principles; lifestyle migration; traditional knowledge